Aliran Romantisisme: Historisitas, Karakteristik, dan Pengaruhnya terhadap Sastra Arab - Nisa', Ida Chairun; Fathurrahman, M. Syauqi (Study Program of Arabic Language Teaching, 2024)
This study explains the beginning of the emergence of romanticism in the Arab world, details its characteristics, and describes some of the influences of romanticism on Arabic literature. This type of research is descriptive qualitative using a library research approach. The data in this research is in the form of historical discourse, its characteristics, and its influence on Arabic literature. Data sources were taken from several books and e-journals. Data collection techniques are carried out using documentation. Data analysis was carried out in 4 stages: data reduction, data presentation, validation and confirmation of conclusions. This research shows that romanticism emerged in the Arab world around the 20th century, brought by Khalil Mutran. This school opposes classicism, which limits the space for expression in poetry. The prominent characteristics of this school are At-Tabi’iyyah, Al-’āṭifah, Al-Khayāl, creative and free. Among the influences of romanticism is the rise of several romanticist literary movements that essentially reinforce the presence of romanticism. In addition, there was a renewal of magazines and newspapers.